POLARIZATION OF LOCAL COMMUNITY ORIENTATION TO THE DEVELOPMENT OF ECO-RURAL TOURISM IN KERINCI REGION, JAMBI PROVINCE, INDONESIA - Bonanza, Occy; Avenzora, Ricky; Malihah, Elly; Hermawan, Rachmad (Indonesian Journal of Forestry Research, 2024)
Rural areas are increasingly the focus of exploration by various stakeholders. However, local communities, as landowners in these regions, often do not reap the full benefits. This issue stems from their limited involvement in regional development and a lack of awareness about ongoing projects. Local communities play a crucial role in the success of rural development, and understanding their attitudes is vital.This study aimed to explore local community attitudes toward eco-rural tourism development in Kerinci Regency, Jambi Province. A closed-ended questionnaire, designed with a "One Score One Indicator" system, assessed various factors including socio-cultural aspects, conservation, ethnic politics, economics, regional development, tourism, and landscape ecology across six villages. The analysis of local community orientation was conducted using quantitative descriptive methods and One-Way ANOVA statistical tests.Results indicated a positive polarization in community attitudes across all villages, showing strong support for eco-rural tourism. By focusing on the identified indicators, local communities are motivated to collaborate and enhance their rural areas through eco-tourism initiatives. The findings suggest that these communities possess significant potential to develop their regions in line with eco-rural tourism principles. Additionally, the insights gained can inform the creation of eco-rural tourism programs that emphasize community involvement and leverage local strengths. This approach aims to ensure that rural communities benefit from the exploration and development occurring in their areas.